Learning Will Continue - Mischel Miller; Debbie K Mercer (The Advocate, 2020)
When Kansas school buildings were closed for the remainder of spring 2020, school leaders responded to ensure learning would continue for the P-12 500,000 students. Rapid change research provides a framework for looking at the response needed during this pandemic. The Kansas State Department of Education led efforts to pivot to remote learning. This article analyzes research data from all public and private schools related to challenges during this time. Access to technology, both devices and internet, remote delivery modes for teaching and learning, and use of paper packets are discussed as the State strengthens and moves forward.
Keywords: school change; COVID-19 response; technology access